2002
DOI: 10.3390/70700511
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Studies on Optically Active Schiff-base Ligands Derived from Condensation of 2-Hydroxyacetophenone and Chiral Diamines

Abstract: Three optically active Schiff-base ligands have been prepared by condensation of 2-hydroxyacetophenone with (1R,2R)-(-)-1,2-diaminocyclohexane, (1S,2S)-(-)- 1,2-diphenylethylenediamine or  R-(+)-2,2’-diamino-1,1’-binaphthalene, respectively. The products have been characterized by their IR, 1H- and 13C-NMR spectra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
35
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 10 publications
0
35
0
Order By: Relevance
“…Since the electron donor and electron acceptor properties of the ligand, structural functional groups and the position of the ligand in the coordination sphere together with the reactivity of coordination compounds may be the factor for different studies [8,9]. Schiff bases are an important class of ligands, such ligands and their metal complexes having a variety of applications including biological, clinical, analytical and industrial in addition to their important roles in catalysis and organic synthesis [10][11][12][13][14][15][16][17]. The first Schiff base metal complexes were already prepared and described in the literature by Schiff in 1864 [18].…”
Section: Introductionmentioning
confidence: 99%
“…Since the electron donor and electron acceptor properties of the ligand, structural functional groups and the position of the ligand in the coordination sphere together with the reactivity of coordination compounds may be the factor for different studies [8,9]. Schiff bases are an important class of ligands, such ligands and their metal complexes having a variety of applications including biological, clinical, analytical and industrial in addition to their important roles in catalysis and organic synthesis [10][11][12][13][14][15][16][17]. The first Schiff base metal complexes were already prepared and described in the literature by Schiff in 1864 [18].…”
Section: Introductionmentioning
confidence: 99%
“…Among these ligands the linear and cyclic Schiff bases obtained by the condensation of primary amines with aldehydes, and their associated metal complexes, find a variety of applications including biological, clinical, analytical and industrial, in addition to their important role in catalysis and organic synthesis [5,6]. The metals in these complexes act as active sites and thereby catalyse chemical reactions [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Survey of the literature reveals an excellent work devoted to synthesis and characterization of many metal complexes of Schiff base [14][15][16][17]. Additionally, it has been reported that Schiff bases and their first-row transition metal complexes can exhibit fungicidal, bactericidal, antiviral and antitumor activities in addition to their important roles in catalysis and organic synthesis [18][19][20]. Metal complexes of Schiff bases derived from substituted salicylaldehydes and various amines have been widely investigated because of their wide applicability [21][22][23] especially metal complexes of Schiff bases with heterocyclic compounds find applications as potential drugs [24].…”
Section: Introductionmentioning
confidence: 99%